Práticas de intervenção no património edificado, a cargo de entidades públicas. Dois casos no centro histórico do Porto. - Maria João Pedro Soares (2013)
This study starts with the desire to know the course and evolution of the urban regeneration in the city of Porto, focusing on its interventions in the housing tissue with patrimonial character. In this context, the analysis is carried out before different actions over a group of buildings in physical declination, which belong mostly to older tissues, having an insignificant recognition as a cultural value, conditioning and being conditioned by an over occupation and an insufficient supply of housing quality. In the beginning of 20th century entered a force into Portugal with a will to renew the unhealthy areas of the cities by setting up hygienist plans. It's in the 60s that the intervention in the historical centers begins to show differences in its objectives and principles, showing the preeminence of safeguarding the architectural heritage existing in these areas. This period coincides with a crucial stage in the evolution of the urban rehabilitation concept. After the April Revolution emerges the first institutions that provides the attention given to the concerns of the residents, whose stay is compromised by the actions of urban regeneration. This work is about that movement in the city of Porto and its development until now. Throughout this chronological path, there is a duality of strategies, prompted by different needs and interests. Taking into account this situation, two public entities have been selected for analysis, the CRUARB and Porto Vivo, SRU, which over the historical conglomerate of Porto, in its former operations, shows this divergence. This work is based on the demand for specific modes of action and architectural preservation, as well as their implications in the social and urban tissue, given particular attention to two cases that represent each approach: plots of Quarteirão QIII of Operação Ribeira-Barredo and Unidade de Intervenção do Quarteirão Carlos Alberto. In fact, the rehabilitation of buildings is a crucial component of urban regeneration. However, in the central conglomerate of Porto, we identify issues also outside their physical dimension. It is believed these spaces should be restructured and appropriated in a social and cultural level, depending on a realistic analysis that promotes the necessary transformations and maintains its relevance.